Doublex Sequencing in Molecular Diagnosis of Hereditary Diseases. (May 1998) - Plaschke, J.; Voss, H.; Hahn, M.; Ansorge, W.; Schackert, H.K.
We describe doublex sequencing of human genomic PCR products using two differently labeled primers in a single reaction and analysis on two automated DNA sequencing devices. Feasibility of the methodology is demonstrated by isothermal and cycle sequencing for two different PCR products and by cycle sequencing on both strands of a single product. It was applied to analyze mutations in patient DNAs in routine sample screening. Because it has the advantage of increased throughput and cost reduction while retaining its accuracy and reading length, we found that doublex sequencing is an attractive option for molecular diagnosis of hereditary diseases. This approach would be even more beneficial if it used DNA sequencing devices with several lasers in a single instrument.